Model Pembelajaran Kooperatif Tipe Take and Give Meningkatkan Prestasi Belajar Siswa pada Mata Pelajaran Ilmu Pengetahuan Sosial - Ira Fitria Sofiani; Qoriati Mushafanah; Kiswoyo Kiswoyo (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
The low learning achievement of students in social science subjects (IPS) is caused because students are less interested in the material. After all, the method does not support so that learning is not effective. The purpose of this study is to analyze the increase in learning achievement in social studies subjects for class IV during online learning by applying the take and give a type of cooperative learning model. This type of research is qualitative research. The research population is class IV which consists of 27 students. The data in this study were obtained through documentation, observation, and interviews. The results showed that students became more active in commenting in the Whatsapp group when they felt curious, asked things they did not understand, and asked whether the answer was correct or not. Students feel more interested because the presentation of images is presented in the form of cards which is certainly different from the images that are usually sent by teachers from Google. Student achievement also increases because students learn through the process of observing pictures, analyzing information, gathering information, communicating to their partner's friends, and automatically conducting discussions to match whether the cards are the correct pairs. Based on the results of the study, it can be concluded that the application of the take and give learning model improves the learning achievement of fourth-grade students in social science subjects (IPS) during online learning.